Crescimento, produção e qualidade de frutos de tomateiro em cultivo adensado com uso de paclobutrazol - Carneiro Ferreira, Nozimary; Pradi Vendruscolo, Eduardo; Seleguini, Alexsander; Souza Dourado, Wilson de; Sabin Benett, Cleiton Gredson; Reis Nascimento, Abadia dos (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 72-79.